2016
DOI: 10.1039/c6ra08124j
|View full text |Cite
|
Sign up to set email alerts
|

High-density polyethylene/needle-like sepiolite clay nanocomposites: effect of functionalized polymers on the dispersion of nanofiller, melt extensional and mechanical properties

Abstract: The present article reports the preparation of high density polyethylene (HDPE)/sepiolite-clay nanocomposites with improved mechanical performance and melt extensional properties by melt compounding using a co-rotating twin screw extruder. Maleic anhydride grafted high density polyethylene (HDPE-g-MA) (having different MFI and maleic anhydride content) was used as compatibiliser to investigate systematically the effect of polarity and molecular weight on the properties of HDPE/sepiolite nanocomposites. The inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The selective distribution of inorganic nanoparticles can regulate the morphology of the dispersed phase and further improve the compatibility of blends [28,29,30,31,32,33,34,35,36]. It has been reported that many nanoparticles, including SiO 2 , ZnO, CaCO 3 , carbon nanotubes, and montmorillonite, could induce β -nucleation in PP, which resulted in higher crystallization rates [37,38,39,40,41,42,43,44,45,46]. Due to the large specific surface, high surface activity, and lack of abrasion, sepiolite (Sep) is an ideal enhancer for polymers [47,48,49,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…The selective distribution of inorganic nanoparticles can regulate the morphology of the dispersed phase and further improve the compatibility of blends [28,29,30,31,32,33,34,35,36]. It has been reported that many nanoparticles, including SiO 2 , ZnO, CaCO 3 , carbon nanotubes, and montmorillonite, could induce β -nucleation in PP, which resulted in higher crystallization rates [37,38,39,40,41,42,43,44,45,46]. Due to the large specific surface, high surface activity, and lack of abrasion, sepiolite (Sep) is an ideal enhancer for polymers [47,48,49,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the majority of research on clay-filled composites has primarily utilized natural layered silicate clays, such as montmorillonite (MMT). In most instances, these fillers have served as reinforcing agents in polymeric matrices, yet significant advancements in the field remain elusive. On the other hand, sepiolite emerges as a promising material with applications spanning a wide spectrum due to its sorptive, rheological, and catalytic properties. While sepiolite is a member of the clay family, it exhibits a fibrous characteristic that is distinct from that of conventional plate-like particles. The structure of this material is composed of two tetrahedral silica sheets and a central octahedral sheet with magnesium.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, sepiolite emerges as a promising material with applications spanning a wide spectrum due to its sorptive, rheological, and catalytic properties. 15 18 While sepiolite is a member of the clay family, it exhibits a fibrous characteristic that is distinct from that of conventional plate-like particles. The structure of this material is composed of two tetrahedral silica sheets and a central octahedral sheet with magnesium.…”
Section: Introductionmentioning
confidence: 99%